PHASING OUT KEROSENE SUBSIDY IN DEVELOPING COUNTRIES CASE STUDY OF INDIA AND INDONESIA - Sujai, Mahpud (Badan kebijakan Fiskal, 2011)
Subsidy is one of the main problems that burden the budget in some developing countries. Indonesia and India have similarities in dealing with efforts to reduce energy subsidies, especially kerosene. This study aims to explain the impact of the kerosene subsidy to the state budget of India and Indonesia, to explore and propose the alternative solutions to solve the problems occurred in relation with the implementation of the kerosene subsidy in both countries and to elaborate the strategy made by the government of both countries in reducing kerosene subsidy. This study used qualitative methods to explore ways of collecting information through data analysis in various types of both primary and secondary. The analysis used in this research is descriptive analysis in which researchers performed interpretation of data. From the analysis conducted, both countries succeeded in reducing the burden of subsidies for kerosene with a variety of strategies fit with the characteristics of each country.